DETERMINAN KINERJA PENGELOLAAN KEUANGAN DESA DI KECAMATAN BANDAR PUSAKA KABUPATEN ACEH TAMIANG - Anisa; Iqlima Azhar; Nasrul Kahfi Lubis; Nurjannah (Jurnal Mahasiswa Akuntansi Samudra, 2025)
This study aims to determine the effect of leadership style, village apparatus competence, and transparency on village financial management performance in villages in Bandar Pusaka District, Aceh Tamiang Regency. This study uses quantitative methods using data obtained from questionnaires, the population in this study were all villages in Bandar Pusaka sub-district, involving 60 respondents from all villages. this study uses multiple linear regression analysis and the data is processed using the SPSS application. The results of this study indicate that leadership style, apparatus competence and transparency have a significant positive effect on village financial management performance, both partially and simultaneously. This research has several limitations that need to be recognised. Firstly, the scope of the study is limited, so the results may not be generalisable to other kecamatan or kabupaten with different characteristics. In addition, the quantitative approach used does not reveal other qualitative dynamics or factors that could provide a deeper understanding of village financial management behaviour. Future research is recommended to expand the study area so that the results are more representative for a wider regional context. In addition, it is recommended to add other variables to the research model to provide a more comprehensive picture of the factors that influence village financial management performance. The use of mixed methods can also be considered to explore qualitative information that can enrich quantitative analysis, resulting in more in-depth and applicable findings for the development of village governance.